Improved Plasmonic Hot-Electron Capture in Au Nanoparticle/Polymeric Carbon Nitride by Pt Single Atoms for Broad-Spectrum Photocatalytic H2 Evolution - Gao, Manyi; Tian, Fenyang; Zhang, Xin; Chen, Zhaoyu; Yang, Weiwei; Yu, Yongsheng (Nano-Micro Letters, 2023)
Rationally designing broad-spectrum photocatalysts to harvest whole visible-light region photons and enhance solar energy conversion is a “holy grail” for researchers, but is still a challenging issue. Herein, based on the common polymeric carbon nitride (PCN), a hybrid co-catalysts system comprising plasmonic Au nanoparticles (NPs) and atomically dispersed Pt single atoms (PtSAs) with different functions was constructed to address this challenge. For the dual co-catalysts decorated PCN (PtSAs–Au2.5/PCN), the PCN is photoexcited to generate electrons under UV and short-wavelength visible light, and the synergetic Au NPs and PtSAs not only accelerate charge separation and transfer though Schottky junctions and metal-support bond but also act as the co-catalysts for H2 evolution. Furthermore, the Au NPs absorb long-wavelength visible light owing to its localized surface plasmon resonance, and the adjacent PtSAs trap the plasmonic hot-electrons for H2 evolution via direct electron transfer effect. Consequently, the PtSAs–Au2.5/PCN exhibits excellent broad-spectrum photocatalytic H2 evolution activity with the H2 evolution rate of 8.8 mmol g−1 h−1 at 420 nm and 264 μmol g−1 h−1 at 550 nm, much higher than that of Au2.5/PCN and PtSAs–PCN, respectively. This work provides a new strategy to design broad-spectrum photocatalysts for energy conversion reaction. Highlights: 1 A hybrid co-catalysts system comprising Au nanoparticles (NPs) and PtSAs with different functions was constructed on the polymeric carbon nitride (PCN) surface by double-solvent method. 2 For the dual co-catalysts, the Au NPs absorb relatively long-wavelength light to produce plasmonic hot-electrons, and the adjacent Pt single atoms (PtSAs) can trap the plasmonic hot-electrons effectively for H2 evolution. 3 The PtSAs–Au2.5/PCN exhibits excellent broad-spectrum photocatalytic H2 evolution activity with the H2 evolution rate of 8.8 mmol g−1 h−1 at 420 nm and 264 μmol g−1 h−1 at 550 nm, respectively.